Profit considerations in vaccine safety-related events in China. (2nd November 2019) - Zhuang, Jianlin; Lu, Yihan; Wagner, Abram L; Jiang, Qingwu
ABSTRACT: Objectives : China has made remarkable achievements in the field of immunization. However, several widespread vaccine safety-related events have recently received worldwide attention and reflect flaws in vaccine management. This study aimed to summarize vaccine safety-related events between 1985 and 2018 in China and analyze the profit motives of these events. Methods . Literature and media reviews were conducted to discover vaccine safety-related events. We developed a conceptual model with profit-related variables, and using information available from each event, we identified which profit-related variable was implicated, and how it related to the pursuit of higher profits. Results : A total of 39 vaccine safety-related events were found in vaccine production, procurement, transportation, and daily management, along with adverse events following immunization (AEFIs). Overall, 90% (35/39) of the events could be classified as profit-driven. The motives of most events could be tied to one or more reasons, including decreasing costs among vaccine producers (67%, 26/39), reducing actual procurement price (67%, 26/39), and reducing costs of transportation and/or cold chain (24/39, 62%). Conclusions : In order to deal with vaccine-related challenges, a more restrictive supervision system on vaccine production and more emergency preparedness, including health and risk communication strategies, for vaccine safety should be implemented.